Identifying and tracking the urban–rural fringe evolution in the urban–rural transformation period: Evidence from a rapidly urbanized rust belt city in China - Xingjia Wang; Dongyan Wang; Jiaxi Lu; Wanying Gao; Xiaotong Jin (Ecological Indicators, 2023)
Urban–rural fringe, the frontier space for urban–rural linkage and the ecological barrier for urban–rural integration, is the most intensive area of man–land conflicts. Its scientific identification and dynamic monitoring are of great significance for balancing urban and rural development and spatial governance in the new era of China. However, existing demarcation methods are often limited to territorial uniqueness and not conducive to replication and reconstruction, making it difficult to determine the boundary accurately and objectively, let alone carry out the longitudinal comparison of the identification results. In this context, this research introduced the iterative unsupervised classification method and central gravitational agglomeration, combined with the land use information entropy model, to realize the urban–rural fringe identification of the long-time series of low-density development-type cities. Changchun city as a typical rust belt city in Northeast China was chosen as an example to identify and track the development pattern of its urban–rural fringe from 1990 to 2020. Meanwhile, time-series land use transfer and landscape analyses were applied to comparatively measure the spatial variations of stable, expanded, and reduced urban–rural fringes. The results indicated that Changchun has undergone significant peri-urbanization over the past 30 years. The urban–rural fringe primarily presented a significant ring-belt shape with continuous outreach features which could be described as “inner circle subtraction, internal hollow filling, leaping expansion, and extension spreading” types of evolution. The land use structure was mainly manifested by an obvious ecological degradation and the internal conversion in stable urban–rural fringe was particularly prominent. As the result of uninterruptedly exogenous and endogenous conflicts, the spatial arrangements were increasingly fragmented, complex, and heterogeneous, whereas these phenomena were slightly alleviated during 2015–2020, especially in stable and expanded urban–rural fringes. These findings intend to assist in the regeneration of rust belt cities and provide a reference for the new urban–rural planning system.